Enriching Entrepreneurship Education: Unravelling the Effect of Entrepreneurial Storytelling on Entrepreneurial Intention through Entrepreneurial Passion, Self-Efficacy, and Attitude - Uzoma Heman Ononye; Dumebi Ezar Ehiagiator (Petra International Journal of Business Studies, 2025)
Entrepreneurship education is critical to a nation's economic growth and development, but the challenge lies in enriching it to ensure that individuals resonate with the idea of entrepreneurship. This study examines the effect of entrepreneurial storytelling on entrepreneurial intention, with a focus on the mediating roles of entrepreneurial passion, self-efficacy, and attitude. The study utilized cross-sectional data from a sample of 364 students at Delta State University in Nigeria, and the partial least squares technique was employed to test the hypotheses. The study found that entrepreneurial storytelling had no direct effect on entrepreneurial intention but had indirect effects through the interplay among entrepreneurial passion, self-efficacy, and attitude. The study concluded that entrepreneurial storytelling partially enhances entrepreneurial intention by strengthening entrepreneurial passion, self-efficacy, and attitude.